Collapsing focal segmental glomerulosclerosis: Increasing the awareness - Muhammed Mubarak (Society of Diabetic Nephropathy Prevention, 2012)
Collapsing focal segmental glomerulosclerosis (cFSGS), also known as collapsing glomerulopathy (CG) is of considerable interest for a variety of reasons. Its incidence is on the rise, and in many parts of the world, it has emerged as one of the leading causes of end-stage renal disease (ESRD). There is currently no specific treatment and the response to standard immunotherapeutic agents is poor. Majority of the cases have been reported from the western countries, but the lesion is also being increasingly recognized in the tropical regions. It is imperative to increase the awareness of the lesion among the pathologists and the nephrologists from the developing countries for its accurate diagnosis and appropriate prognostication.